The Treasure Chest Supplementary Reading Material - Roderick Hunt; Roderick Hunt (Oxford Reading Tree, 2012)
There is a magic key and when it glows there's an adventure. They found a treasure chest inside was lots of gold. Then the children went back home. I enjoyed this book. King Chip Postage $1! =s